Business Strategy to Achieve the Target Time of Laytime Allowed for Coal Commodities - Subastian, Djamal; Anindya, Badzlina; Najoan, Denny J.; Farisyi, Sofwan; Ichwan, Gema Akbar (Jurnal Manajemen Transportasi & Logistik (JMTRANSLOG), 2025)
For the logistics process, the company needs to pay attention to the loadings process to achieve the laytime that has already been agreed between the parties. In the logistics process, the company often gets the problem which is not an accordance mismatch between the plan and actual in the process of coal loading. As a result, the company must pay demurrage due to the laytime used for the loading process over the laytime allowed. This research aims to determine a business strategy to achieve the target laytime of the coal loadings. This author used SWOT analysis for this research by analyzing external factors and internal factors. The author uses descriptive qualitative analysis as a data analysis method. The result of this strategy formulation is backward integration. The author used matrix IFE EFE and matrix SWOT as tools for making strategies.  The implementation is the company needs to acquire a jetty around the coal mine by using the profit from increasing profit so that the coal in the stockpile can accommodate large amounts of the coal and can be distributed quickly.